1

Exercises ...
Systems of Linear Equations 2 ×
o ms convenient. 5 x + 2 y = 17
+ 1 and = 3 3 x - 1 = 22 1 x +
1 y = x + 1 -39 3 -4 -1 y = x -25 -3 x + 3 y = -45 5 x + 1 y
1 6 x + 2 y = 36 2 x + 2 = 20 1
= 15 2 x + 2 y = -16 5 x + 1 y

2 Directions: Solve the following algebraic mtod
-6 x + 2 y = 6 6 x + 4 y = x + 1 -14 1 -5 y = 2x
1 y = 10 -5 x - 2 y = x + 2 -38 2 -30 y = 5 x +
4 y = -6 2 x + 4 y = 38 2 x + 2 = 26 1 x + 4 y =
= 24 -4 x - 1 y = -20 2 x + 1 = 19 4 x - 1 y = 1
x + 1 y = -8 -1 x - 1 y = 8 4 x + 1 = 20 1 x - 1
= -4

Exercises ...
• • • • • • • • • • • • • •
x = 1, y = 6 x = 3, y = -8 x = 5, y = -7 x = 6, y = 4 x = -6, y = -9 x = -2, y =
2 x = 7 , y = 6 x = 7, y = -8 x = 4, y = 4 x = 5, y = 9 x = 4, y = 6 x = 1, y =
-9 x = 7, y = -8 x = 1, y = -9
Exercises
Prohibited commercial use of this material.
A. Soto Efran
2
• • • • • • • • • • • • • • • • •
1 x + 4 y = -21 -4 x + 1 y = 1x + 2y = 16 2 -1 x + 3 y = -2 2 x + 2 y = 16 1 x +
3 = 12 3 x + 2 y = 24 -2 x + 1 y = -9 3 x + 4 y = -3 -2 x + 1 = 13 6 x + 1 y =
35 3 x - 4 = 22 3 x + 2 y = -13 -1 x + 3 y = x + 1 -3 3 -1 -2 y = x - 2 y = 2 4
x + 1 y = -27 6 x - 3 y = -63 1 x + 4 y = -39 -3 x -9 + 2 y = 2 x + 1 y = 14 1x
- 4y = 7 1 x + 4 y = -8 -2 x + 1 y = 16 3 x + 1 y = -21 -3 x - 1 y = 21 4x = 4 4
x + 1 and - 1 and = 4 1 x + 1 y = -4 -5 x - 1 y = 4 3 x + 4 y = -39 -4 x + 2 y =
8 1x + 1y = 2 -2 x - 2 y = -4
x = -5, y = -4 x = 2, y = 0 x = 6, y = 2 x = 6, y = 3 x = -5, y = 3 x = 6, y = 1 x = -3 , y = -2 x = 0, y = -1 x = -8, y = 5 x = -3, y = -9 x = 7, y = 0 x = -8
, y = 0 x = -5, y = -6 x = 1, y = 0 x = 0, y = -4 x = -5, y = -6 x = 0, y = 2
Exercises
Prohibited commercial use of this material.
A. Soto Efran
3
• • • • • • • • • • • • • • • • •
1x + 2y = 2 -6 x + 4 = 20 3 x + 1 y = -20 -6 x - 1 y = 35 4 x + 1
= 32 2 x + 1 y = - June 17 x - 1 y = x + 4 -23 4 -60 y = 3 x + 4
1 y = -3 3x - 1 and = 3 6 x + 3 y = -24 1 x - 4 y = -31 4 x + 1 y
= 15 4 x + 1 = 30 3 x - 4 y = -6 5 x + 1 y = 36 -2 x - 3 y = -30
7 -4 x + 3 y = 11 1 x + 3 y = -11 -5 x - 3 y = 7 3x + 2y = 1 -3 x
4y = 8 2x + 2y = 4 5x + 1y = 8 -1 x - 4 y = x + 1 -13 3 -36 -6 y
4 x + 1 y = 40 6 x - 1 y = 40

=
y
=
3
+
=

13 5 x - 1 y
= -51 2 x +
-5 4 x - 3 y
x + 4 y = -2
3 y = 9 4x +
x - 2 y = 72

x = -2, y = 2 x = -5, y = -5 x = 5, y = -7 x = -5, y = -7 x = -9, y = -6 x = 0,

y = - 3 x = -7, y = 6 x = 0, y = -5 x = 6, y = 6 x = 6, y = 6 x = -5, y = -3 x =
1, y = -4 x = -1, y = 2 x = -5, y = 7 x = 1, y = 3 x = -9, y = -9 x = 8, y = 8
Exercises
Prohibited commercial use of this material.
A. Soto Efran
4
• •
6 x + 1 y = -44 4 x - 1 y = 2 -16 4 x + y = -8 1 x + 2 y = -11
x = -6, y = -8 x = 1, y = -6
Exercises
Prohibited commercial use of this material.
A. Soto Efran